2012
DOI: 10.1590/s1677-55382012000400019
|View full text |Cite
|
Sign up to set email alerts
|

Ventral phalloplasty

Abstract: _______________________________________________________________________________Purpose: To present the surgical technique of ventral phalloplasty as an adjunct procedure to the classic prosthetic surgery. Materials and Methods:In this video we demonstrate how to perform a ventral phalloplasty in a patient that has undergone a penile prosthesis implantation. Our technique consists of: delineation of the penile scrotal web, excision of this redundant skin, and re-approximation of the wound to mimic the natural m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
(5 reference statements)
0
1
0
Order By: Relevance
“…Vental phalloplasty, a procedure based on the common pediatric procedure to correct a webbed penis, involves surgical release of the ventral penoscrotal web. First described in 2007 as an adjuvant designed to increase patient satisfaction with IPP placement, several studies have shown that ventral phalloplasty increases perceived penile length in the majority of patients ( 61 , 64 - 66 ). However, patients who receive ventral phalloplasty are at high risk for wound dehiscence, especially if there are diabetic.…”
Section: Adjuvant Therapies To Increase Penile Lengthmentioning
confidence: 99%
“…Vental phalloplasty, a procedure based on the common pediatric procedure to correct a webbed penis, involves surgical release of the ventral penoscrotal web. First described in 2007 as an adjuvant designed to increase patient satisfaction with IPP placement, several studies have shown that ventral phalloplasty increases perceived penile length in the majority of patients ( 61 , 64 - 66 ). However, patients who receive ventral phalloplasty are at high risk for wound dehiscence, especially if there are diabetic.…”
Section: Adjuvant Therapies To Increase Penile Lengthmentioning
confidence: 99%